2022
DOI: 10.1101/2022.01.01.22268600
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How To Enhance Empathy Nursing Students In Education: Literature Review

Abstract: Introduction. The tendency of reducing student empathy requires efforts to improve it through education or training. The purpose of this review is to identify education, learning, or teaching that is used to increase student empathy. Method. The design used a Literature Systematic Review. Articles were conducted in three electronic databases guided by The PRISMA. Articles published in English and from 2019 to 2021. Results. The result obtained 20 articles and will be reviewed. Eighteen articles show an effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In the present cross‐sectional study, it can be seen in the studied sample that female physiotherapy students at the University present more significant empathic development than male students, something which agrees with the results of Chu et al 39 However, in this study by Chu et al, an improvement in empathic development was observed among male physiotherapy students after having received training in communication skills and improved empathic thinking. Therefore, the authors believe it is right to continue innovating and implementing training to enhance the students' communication skills and critical and empathic thinking, as other authors have also reported 26,40‐47 …”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In the present cross‐sectional study, it can be seen in the studied sample that female physiotherapy students at the University present more significant empathic development than male students, something which agrees with the results of Chu et al 39 However, in this study by Chu et al, an improvement in empathic development was observed among male physiotherapy students after having received training in communication skills and improved empathic thinking. Therefore, the authors believe it is right to continue innovating and implementing training to enhance the students' communication skills and critical and empathic thinking, as other authors have also reported 26,40‐47 …”
Section: Discussionmentioning
confidence: 92%
“…Therefore, the authors believe it is right to continue innovating and implementing training to enhance the students' communication skills and critical and empathic thinking, as other authors have also reported. 26,[40][41][42][43][44][45][46][47] In addition, the fact that the students are working or have work experience in another health profession while studying for their degree in physiotherapy means they obtain lower scores on the IRI subscale of personal distress (PD). This issue is closely related to the conclusions of the studies'.…”
Section: Pairwise Comparisonsmentioning
confidence: 99%
“…Therefore, as stated in the literature, health professionals need to be sensitive to social and cultural differences [ 15 ]. The fact that 55 participants answered that they do not make mistakes suggests a lack of awareness of mistakes, which is also related to empathy [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Empathy, as the essence of effective therapeutic communication, is a crucial skill for nurses (1,2). Many studies reported that health workers' empathy is directly associated with better patient outcomes (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%